Ontogenetic δ15N Trends and Multidecadal Variability in Shells of the Bivalve Mollusk, Arctica islandica - Schöne, Bernd R.; Huang, Qian (Frontiers in Marine Science, 2021)
Bulk stable nitrogen isotope values of the carbonate-bound organic matrix in bivalve shells (δ15NCBOM) are increasingly used to assess past food web dynamics, track anthropogenic nitrogen pollution and reconstruct hydrographic changes. However, it remains unresolved if the δ15NCBOM values are also affected by directed ontogenetic trends which can bias ecological and environmental interpretations. This very aspect is tested here with modern and fossil specimens of the long-lived ocean quahog, Arctica islandica, collected from different sites and water depths in the NE Atlantic Ocean. As demonstrated, δ15NCBOM values from the long chronologies show a general decrease through lifetime by −0.006‰ per year. The most likely reason for the observed δ15NCBOM decline is a change in the type of proteins synthesized at different stages of life, i.e., a gradual shift from proteins rich in strongly fractionating, trophic amino acids during youth toward proteins rich in source amino acids during adulthood. Aside from this ontogenetic trend, distinct seasonal to multidecadal δ15NCBOM variations (ca. 50 to 60 years; up to 2.90‰) were identified. Presumably, the latter were governed by fluctuations in nutrient supply mediated by the Atlantic Multidecadal Variation (AMV) and Atlantic Meridional Overturning Circulation (AMOC) combined with changes in nitrate utilization by photoautotrophs and associated Rayleigh fractionation processes. Findings underline the outstanding potential of bivalve shells in studies of trophic ecology, oceanography and pollution, but also highlight the need for compound-specific isotope analyses.